Unveiling the Hidden Meanings Behind the Karembong Beureum Illustration: A Study of Visual Communication Semiotics in the Work of Ayi R. Sacadipura - Yudi Rudiyansyah (JOMANTARA, 2025)
Illustrations serve as a powerful form of visual communication, conveying messages and meanings that transcend words. This study delves into the visual expression style of Ayi R. Sacadipura, specifically focusing on the illustration titled "Karembong Beureum." Employing Roland Barthes' Communication Semiotics theory, a descriptive interpretative analysis is conducted to uncover the hidden meanings embedded within the illustration. The analysis reveals how Ayi R. Sacadipura utilizes various visual elements, including color, shape, and composition, to craft and communicate messages effectively. By dissecting the semiotic codes, the study demonstrates how these elements contribute to the overall visual expression style of the artist. Furthermore, the analysis explores potential connections between the visual meanings and societal phenomena, particularly the cultural and social values embedded within the artwork. This study underscores the significance of illustrations as mediums that transcend mere decoration, highlighting their capacity to convey complex messages that can resonate with viewers on an emotional and intellectual level. Keywords: Visual Communication Semiotics, Ayi R. Sacadipura, Karembong Beureum Illustration, Visual Expression Style